The Role of Fiscal Space in Attracting FDI - Fattah, Engy Raouf Abdel (Asian Journal of Economic Modelling, 2017)
Attention has been given to the attraction of foreign direct investments for many countries worldwide. The main objective of this paper is to examine the relationship between fiscal space and FDI in a number of developing countries. A principal component analysis across official development assistance (ODA), domestic revenue mobilization, deficit financing whether domestic or foreign, and reprioritization and efficiency of expenditures has been used to derive an overall fiscal space index. Subsequently, a FE-GLS model has been employed for a panel data of 50 developing countries over the period from 2000 to 2016. The regression shows that fiscal space and its four pillars have positive, significant impact on attracting FDI.